Seroprevalence of Infectious Bronchitis Virus in Broiler Farms in Batna, East Algeria - Barberis , Abdelheq; Alloui, Nadir; Boudaoud, Amine; Bennoune, Omar; Ammar, Ayachi (International Journal of Poultry Science, 2018)
Background and Objective: Avian infectious bronchitis is an infectious viral disease that induces major economic losses. It has a worldwide distribution and a high morbidity rate, that may reach 100%. Infectious bronchitis monitoring and typing are needed to determine its impact on the chicken industry and to choose adequate vaccine strains. The aim of this study was to determine the existence of the disease and to monitor its seroprevalence in unvaccinated broiler farms in the East of Algeria. Methodology: The study was conducted in the province of Batna (East of Algeria). One hundred and eighty-four blood samples were collected from different broiler farms and assayed by an indirect ELISA test. Results: Serological analysis showed a high rate of infection with high Infectious Bronchitis Virus (IBV) antibody titers. A total of 144 were positive (78.25%) with a significant average antibody titer (2080.277). Conclusion: The current study demonstrated a high seroprevalence of infectious bronchitis in unvaccinated broiler farms in the East of Algeria. Therefore, adequate preventive measures (vaccination, improvement of hygienic conditions) must be applied to reduce circulation of t the virus and the rate of infection.